Cote d'Ivoire : Enhanced Initiative for Heavily Indebted Poor Countries; Decision Point Document. (IMF Staff Country Reports; Country Report ;, 2009)
This paper examines Cote d'Ivoire's debt sustainability analysis undertaken in connection with the Enhanced Initiative for Heavily Indebted Poor Countries. The crisis years led to a substantial increase in poverty and deterioration in living standards. The March 2007 Ouagadougou Political Accord provides a roadmap for reunification, national reconciliation, demobilization, and elections. Significant revenue efforts and overall expenditure restraint have resulted in a modest space for social and crisis-exit spending. To eliminate extrabudgetary spending in the future and enhance transparency, the authorities have established a range of safeguards.